The Global Branding And Sports Sponsorship: Kelme's Strategy In Responding To The Indonesian National Team - Reva Roudhotun; Reza Arifah Aziz; Nadia Wulandari (POLTRANS: Journal of Politics and Social Transformation, 2026)
The development of the modern sports industry shows that sports no longer function solely as a means of competition and entertainment, but have become part of a global industry involving economic, media, cultural, and marketing interests. In this context, global branding and sports sponsorship strategies have become important instruments for companies to expand their markets and strengthen their brand image. This study aims to analyze Kelme's global branding strategy through its sponsorship partnership with the Indonesian National Team and examine its impact on brand image formation and consumer loyalty. The study uses a qualitative approach with a literature study method that utilizes various sources such as scientific journals, news, company documents, and publications related to the sports industry. The analysis is conducted through a process of data reduction, interpretation, and concluding various relevant information. The results show that Kelme's collaboration with the Indonesian National Team not only functions as a form of sports equipment support but also serves as an effective marketing strategy to increase brand exposure in the Southeast Asian market. The popularity of the Indonesian National Team and the high loyalty of its supporters provide symbolic benefits for Kelme by transferring a positive image and increasing brand awareness among the public. In addition, sports sponsorship can create an emotional closeness between consumers and the brand through the national identity inherent in the Indonesian National Team. This study confirms that sports sponsorship is an effective global branding instrument for strengthening a company's position amid competition in the modern sports industry while building long-term consumer loyalty.